TRPV4 and KRAS and FGFR1 gain-of-function mutations drive giant cell lesions of the jaw. Issue 1 (December 2018) - Gomes, Carolina; Gayden, Tenzin; Bajic, Andrea; Harraz, Osama; Pratt, Jonathan; Nikbakht, Hamid; Bareke, Eric; Diniz, Marina; Castro, Wagner; St-Onge, Pascal; Sinnett, Daniel; Han, HyeRim; et al.
Abstract Giant cell lesions of the jaw (GCLJ) are debilitating tumors of unknown origin with limited available therapies. Here, we analyze 58 sporadic samples using next generation or targeted sequencing and report somatic, heterozygous, gain-of-function mutations inKRAS, FGFR1, and p.M713V/I-TRPV4 in 72% (42/58) of GCLJ.TRPV4 p.M713V/I mutations are exclusive to central GCLJ and occur at a critical position adjacent to the cation permeable pore of the channel. Expression of TRPV4 mutants in HEK293 cells leads to increased cell death, as well as increased constitutive and stimulated channel activity, both of which can be prevented using TRPV4 antagonists. Furthermore, these mutations induce sustained activation of ERK1/2, indicating that their effects converge with that ofKRAS andFGFR1 mutations on the activation of the MAPK pathway in GCLJ. Our data extend the spectrum of TRPV4 channelopathies and provide rationale for the use of TRPV4 and RAS/MAPK antagonists at the bedside in GCLJ. Giant cell lesions of the jaw (GCLJ) are debilitating benign tumors of unclear origin. The authors identify driver recurrent somatic mutations in TRPV4, KRAS and FGFR1 and show they converge on aberrant activation of the MAPK pathway. Their findings extend the spectrum of TRPV4 channelopathies and provide rationale for targeted therapies at the bedside in GCLJ.